Proceedings of the 22nd International Conference on Software Engineering - ICSE '00 2000
DOI: 10.1145/337180.337232
|View full text |Cite
|
Sign up to set email alerts
|

A case study in root cause defect analysis

Abstract: There are three interdependent factors that drive our software development processes: interval, quality and cost. As market Dressures continue to demand new features ever more months. network, consisting of circuit packs, ASICs, software units, and a craft terminal. Total head count for this release was 180 people and the development project lasted for 19 We conclude with lessons learned from the case study and resulting ongoing improvement activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(33 citation statements)
references
References 9 publications
1
30
0
2
Order By: Relevance
“…The defect causal analysis approach is originally a team‐based quality improvement technique used to analyze samples of previous defects, to suggest software process changes and to prevent future defects. The existing literature relevant to software defects causes analysis tended to focus on the taxonomy of causes or the implementation process as a KPA of CMM Level 5 , rather than empirical analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The defect causal analysis approach is originally a team‐based quality improvement technique used to analyze samples of previous defects, to suggest software process changes and to prevent future defects. The existing literature relevant to software defects causes analysis tended to focus on the taxonomy of causes or the implementation process as a KPA of CMM Level 5 , rather than empirical analysis.…”
Section: Related Workmentioning
confidence: 99%
“…[39]. The idea of combining the field of (combinatorial) testing with (root) cause analysis is not new, e.g.…”
Section: Test Evaluationmentioning
confidence: 99%
“…The mistakes were related to human factors -individual errors and lack of domain knowledge about a specific industry and system [1].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the studies under review [1], [8], [9] indicated that the revealed defects were related to testing problems. Other reasons were related with change management, lack of knowledge, requirements faults, data processing problems, and defects in code logic.…”
Section: Introductionmentioning
confidence: 99%